Exploring the Integration of Environmental Identity within EFL Teacher's Identity (Journal of the College of Education for Women, 2022)
Nowadays, the ideas of integrating the concepts of the environment and saving it are being famous. These ideas are widely seen in many fields of study, and language education is one of them. Thus, the identity of English Language teachers (ELT) is a step toward transferring this concept in EFL materials in ELT departments. The EFL teacher's identity takes different meanings. Sometimes, it only means the teacher who teaches the English language, and other times, it means, the cultural and social aspects that the teacher and students interact during the study course. These cultural and social aspects represent the environment in teacher’s identity. This study aims to explore the environmental identity within EFL teacher identity. The sample of 100 student-teachers has been selected randomly from the fourth-grade students in the department of English language in the University of Baghdad. The study tool is adapted from the Environmental Identity Survey (Clayton et al., 2021) and Xun’s  et al. (2014) EFL teacher identity questionnaire. After ascertaining the face validity and reliability of the tool, the study has been applied to the study sample. The results have shown that 16 items of the scale are high, 31 items are moderate, and three of them are low. However, the final results have indicated that student-teachers’ perception of their environmental identity is moderate.